Performance of the cytology and colposcopy compared to histopathology in screening and diagnosis of câncer precursor lesions - Alves, Rosane R.F.; Teixeira, Tamara S.; Netto, Joaquim C.A. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Introduction: the persistem cervical infection by some types of HPV. inducing high-grade intra-epithelial neoplasias. is now considered the etiology of the invasive cervical câncer. The prevention of this câncer is based on screening. diagnosis and treatment of these precursory lesions. through cytology. colposcopy and histological examination of the specimen obtained by directed biopsy. The knowledge of the regional varialion of the basic histological abnormality, in the different cytological categories and colposcopical finding. is importam to supply data to evaluate the guidelines. Objectivc: evaluate the concordance degree and predictive positive value between cytological abnormalities and the colposcopical findings with lhe histopathology. Methods: we studied 794 patients with cytological abnormalities and colposcopy alterations through directed biopsy. endocervical curettage and large loop excision of the transformation zone. when necessary. Results: 742 patients presenting with abnormal colposcopy. From 133 with ASCUS. 15% presented CIN 2/CIN 3 and 2.2%. invasive câncer; from 22 with AGUS. 27% presented CIN 2/ C1N 3 and no câncer; from 332 with LGSIL, 22.5% presented CIN 2/CIN 3 and no câncer, from 255 with HGSIL. 72.1 % presented CIN 2/CIN 3. and 5%. invasive câncer. HGSIL showed predictive positive value of 77.3%. and the larger colposcopical finding, 73.8% forCIN 2/CIN 3 and invasive câncer. Conclusion: patients with ASCUS presented a wide range of histological results. varying from normality to câncer, the ones with AGUS. just cervical intraepithelial lesions; lhe ones with LGSIL and HGSIL presented moderate agreement degree with the histopathological diagnosis of HPV/CIN I and CIN 2/CIN 3. respectively. The smaller colposcopical finding presented fair agreement degree with the histopathological diagnosis of HPV/CIN I. while the larger finding presented moderate agreement degree with CIN 2/CIN 3. The larger colposcopical finding and HGSIL showed high predictive positive value for CIN 2/CIN 3 and câncer.